REGENERASI TANAMAN BELIMBING MELALUI KULTUR AKAR SECARA IN-VITRO - L. Agus Sukamto (BERITA BIOLOGI, 1998)
Star fruit(Averrhoa carambola L.)is considered originally from Indonesia. In-vitro propagation of star fruit- is a very few.Propagation of star fruit through leaf,seedling and cotyledon culture have succeeded but its propagation through root culture has not been reported.This experiment was carried out to know the responses of star fruit root culture.Roots of young seedling of star fruit grown in-vitro were cut and cultured on one-halfMurashige & Skoog (MS)medium with or without addition of1 mg/16-ben^ylaminopurine (BA).The response of explants were determined by age of the seedlings which young seedlings were more response than the old ones. Somatic embryogenesis occurred on explan star fruit roots after 9 weeks incubation. Explants produced little callus on excised roots andprofused multiple shoots on MS with addition of BA, whereas explants only produced a few shoots without any producing callus on medium MS without any addition ofBA. This indicated that star fruit can be propagated from its root which is a very rare success of the other plant regeneration from root culture.